A Nepali Translation of Brief Infant Sleep Questionnaire (BISQ) For Assessment of Sleep in Infants and Toddlers: A Preliminary Report - Dhakal, Ajaya Kumar; Shrestha, Devendra; Shah, Subhash Chandra; Shakya, Henish; Shakya, Arati; Sadeh, Avi (Journal of Kathmandu Medical College, 2015)
Background: Sleep problems are common in children and various questionnaires have been devised to screen these problems. Brief Infant Sleep Questionnaire (BISQ) is one of the sleep screening tools which is simple, reliable and valid tool and is being used for screening of sleep problems in infants and toddlers in various countries. Objectives: The objective of this study was to translate English version of Brief Infant Sleep Questionnaire to Nepali language using a standard technique so that Nepali version could be used to screen sleep problems in Nepalese infants and toddlers. Methods: This article describes the process of translation of original BISQ questionnaire into Nepali language in a standard method. Four bilingual paediatricians translated English BISQ to Nepali language which was then tested among few parents for understanding, clarity and uniformity of expected response. A draft version was finalized after consensus of translators, two expert paediatricians and original author. This version was then translated back into English by two independent medical professionals and compared with original BISQ for content and meaning. The final version of Nepali translation was approved after consensus agreement. Results: The translated Nepali BISQ was then tested among 15 parents who had a child below three years of age. These parents did not find difficulty in understanding and responses were uniform and as expected from the original questionnaire. Conclusion: The Nepali version of BISQ could be applicable as a screening tool to assess sleep in infants and toddlers in clinical setup as well as research studies. DOI: http://dx.doi.org/10.3126/jkmc.v3i3.12245 Journal of Kathmandu Medical College Vol. 3, No. 3, Issue 9, Jul.-Sep., 2014, apge: 102-106